Well productivity handbook : vertical, fractured, horizontal, multilateral, multi-fractured, and radial-fractured wells - Guo, Boyun (Gulf Professional Publishing, 2019)
Well Productivity Handbook: Vertical, Fractured, Horizontal, Multilateral, Multi-fractured, and Radial-Fractured Wells, Second Edition delivers updated examples and solutions for oil and gas well management projects. Starting with the estimation of fluid and reservoir properties, the content then discusses the modeling of inflow performance in wells producing different types of fluids. In addition, it describes the principle of well productivity analysis to show how to predict productivity of wells with simple trajectories. Then advancing into more complex trajectories, this new edition demonstrates how to predict productivity for more challenging wells, such as multi-lateral, multi-fractured and radial-fractured. Rounding out with sample problems to solve and future references to pursue, this book continues to give reservoir and production engineers the tools needed to tackle the full spectrum of completion types. --